2016
DOI: 10.1002/evan.21502
|View full text |Cite
|
Sign up to set email alerts
|

Transparency, usability, and reproducibility: Guiding principles for improving comparative databases using primates as examples

Abstract: This is the accepted version of the following article: Borries, C., Sandel, A. A., Koenig, A., Fernandez-Duque, E., Kamilar, J. M., Amoroso, C. R., Barton, R. A., Bray, J., Di Fiore, A., Gilby, I. C., Gordon, A. D., Mundry, R., Port, M., Powell, L. E., Pusey, A. E., Spriggs, A. and Nunn, C. L. (2016), Transparency, usability, and reproducibility: Guiding principles for improving comparative databases using primates as examples. Evolutionary Anthropology: Issues, News, and Reviews, 25(5): 232-238, which has bee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 61 publications
(103 reference statements)
0
31
0
Order By: Relevance
“…Our analyses substantiate the arguments marshalled by Borries et al . (), who emphazised the need for more careful reliability control with data used in comparative analyses. These authors strongly recommended more transparency in comparative databases, including a better description of the methods applied in the original papers.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our analyses substantiate the arguments marshalled by Borries et al . (), who emphazised the need for more careful reliability control with data used in comparative analyses. These authors strongly recommended more transparency in comparative databases, including a better description of the methods applied in the original papers.…”
Section: Discussionmentioning
confidence: 99%
“…For birds, McKechnie & Wolf () have shown that different scaling equations for BMR may be obtained depending on the severity of data selection. More generally, databases including descriptions and/or evaluations of the conditions under which the original data were obtained have been emphatically recommended (Borries et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Borries, Gordon, and Koenig ()—concerned about the differences they found between their own literature‐based assessments of gestation length estimates for various Asian colobines and macaques and those published in four “popular” life history compilations—attempted to reproduce the analyses in those compilations without success. Some of the problems they found, as well as other issues related to the transparency, usability and reproducibility of comparative analyses are discussed in more detail in a recent publication (Borries et al, ).…”
Section: The Evolution Of “Social Monogamy" In Primates: Contributionmentioning
confidence: 99%
“…For example, in making our own estimates of infanticide risk below, we use both the minimum and maximum reported values for age at weaning; the former “favors” the hypothesis, while the latter “counters” it. We also suggest that, given the paucity of data, authors must make clear the definitions and criteria that are used for assigning data to a taxon, providing explicit and accurate reference to the primary literature where the original data were published (Borries et al, ).…”
Section: The Evolution Of “Social Monogamy" In Primates: Contributionmentioning
confidence: 99%
See 1 more Smart Citation